2021
DOI: 10.3390/ijerph18030935
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health and Psychosocial Functioning in Recently Separated U.S. Women Veterans: Trajectories and Bi-Directional Relationships

Abstract: Prior research on the relationship between veterans’ mental health and psychosocial functioning has primarily relied on male samples. Here, we investigated prospective longitudinal relationships between mental health and psychosocial functioning in 554 female Iraq and Afghanistan War veterans who were surveyed three times between two- and seven-years following separation from service. Mixed effects modeling revealed that increasing depression and posttraumatic stress disorder (PTSD) severity predicted declines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 67 publications
2
9
0
Order By: Relevance
“…In men, scores for severity of PTSD [T1 Mdn = 34, IQR = 23-50; T2 Mdn = 32, IQR = 21-47; T3 Mdn = 31, IQR = 20.2-49.8, P = .002], depression [T1 Mdn = 21.5, IQR = 15-26; T2 Mdn = 19.5, IQR = 13-24.8; T3 Mdn = 19, IQR = 12-25, P < .001], and alcohol misuse [T1 Mdn = 4, IQR = 2-6; T2 Mdn = 3, IQR = 2-5; T3 Mdn = 3, IQR = 1-5, P < .001] symptom severity improved at T2 and T3 relative to T1. As previously reported, 60 in women, scores for depression severity improved at T2 and T3 relative to T1. Women also showed a decrease in the odds of reporting SI at T2 (OR = 0.177, 95% CI: 0.058, 0.493; P = .001) and T3 (OR = 0.225; 95% CI: 0.074, 0.625; P = .006), relative to T1.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…In men, scores for severity of PTSD [T1 Mdn = 34, IQR = 23-50; T2 Mdn = 32, IQR = 21-47; T3 Mdn = 31, IQR = 20.2-49.8, P = .002], depression [T1 Mdn = 21.5, IQR = 15-26; T2 Mdn = 19.5, IQR = 13-24.8; T3 Mdn = 19, IQR = 12-25, P < .001], and alcohol misuse [T1 Mdn = 4, IQR = 2-6; T2 Mdn = 3, IQR = 2-5; T3 Mdn = 3, IQR = 1-5, P < .001] symptom severity improved at T2 and T3 relative to T1. As previously reported, 60 in women, scores for depression severity improved at T2 and T3 relative to T1. Women also showed a decrease in the odds of reporting SI at T2 (OR = 0.177, 95% CI: 0.058, 0.493; P = .001) and T3 (OR = 0.225; 95% CI: 0.074, 0.625; P = .006), relative to T1.…”
Section: Resultssupporting
confidence: 85%
“…At T1, PTSD symptom severity was significantly higher (P = . 60 in women, scores for depression severity improved at T2 and T3 relative to T1. Women also showed a decrease in the odds of reporting SI at T2 (OR = 0.177, 95% CI: 0.058, 0.493; P = .001) and T3 (OR = 0.225; 95% CI: 0.074, 0.625; P = .006), relative to T1.…”
Section: Effects Of Gender On Initial Status and Trajectories Of Mental Health Symptom Severitymentioning
confidence: 89%
See 2 more Smart Citations
“…The present study extends prior research which showed that PTSD and depression symptom severity are bi-directionally related to psychosocial functioning in women veterans ( Lawrence et al, 2021 ). Our objective in this study was to test the hypothesis that a bi-directional association would exist between SI and work, relationship, and parental domains of psychosocial functioning in women veterans, such that worsening functioning would exacerbate subsequent SI, and changes in SI would also impact subsequent psychosocial functioning.…”
Section: Introductionsupporting
confidence: 87%